TEKNIK SUPERVISI AKADEMIK - Fauzi, Anis; Fajriya, Ria; Gunawan, Agus (UII Darullughah Waddawah Pasuruan, 2023)
The results of supervision need to be followed up in order to have a real impact on improving the professionalism of teachers. The follow-up was in the form of reinforcement and appreciation; reprimands of an educational nature; and the opportunity to attend further training or upgrades. The utilization of the results of academic supervision feedback concerns two important activities, namely related to coaching and strengthening academic supervision instruments.The results of supervision need to be followed up in order to have a real impact on improving the professionalism of teachers. The follow-up was in the form of reinforcement and appreciation; reprimands of an educational nature; and the opportunity to attend further training or upgrades. The utilization of the results of academic supervision feedback concerns two important activities, namely related to coaching and strengthening academic supervision instruments.